An econometric analysis of Irish households' food expenditure patterns : Tobit, double-hurdle and infrequency of purchase approaches - Newman, Carol Frances (Trinity College (Dublin, Ireland). Department of Economics, 2002)
In this thesis, the factors shaping Irish households’ meat and prepared meals expenditure decisions are analysed using the 1987/8 and 1994/5 Irish Household Budget Survey datasets. In Chapter 1 of this thesis, the changing pattern of food consumption is outlined and the importance of two sectors of the industry, meat and prepared meals, to the Irish food sector is emphasised. A number of factors are identified as influencing the demand for these food items with the main implication being a decline in the importance of price and income factors and a simultaneous increase in the significance of socio-demographic factors, assumed to underpin consumers’ tastes and preferences. Specifically, convenience and health are identified as significant attributes of food products desired by many household groups. In Chapter 2, the econometric methodology specific to modelling household expenditure using micro survey data, in the presence of zero observations on the dependent variable, is discussed in detail. This entails a description of the three relevant models, the tobit, double-hurdle and infrequency of purchase models, the estimation procedures applied, relevant specification issues and the interpretation of parameters. In Chapter 3, aspects of the 1987/8 and 1994/5 Irish Household Budget Survey datasets are introduced. The sample and variables used in the analyses of the thesis are described with specific attention paid to describing the chosen dependent and independent variables and how they relate to each other.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin